Chemically separating transplutonium elements from rare earth fission products - Hulet, E. K. (Lawrence Livermore Laboratory, 1976)
The existing technology of lanthanide-actinide separations is discussed with emphasis on the difficulties to be expected if the currently practiced separation methods were to be applied to waste partitioning. All of the workable methods known are noted, and three out of the four have seen many applications for the last 20 to 25 years at our Laboratory and elsewhere. The fourth, developed at ORNL 16 to 17 years ago, has been applied to waste partitioning in Germany. Each of these methods depends upon complexing the actinides to a slightly greater extent than the lanthanides with either Cl/sup -/, SCN/sup -/, or aminocarboxylic acids. The separation of the complexed ions is accomplished with either liquid or solid ion-exchangers and, in principle, either can be used interchangeably.